The Curious Case of Confession Bear: Analyzing anonymity and online memes - Vickery, Jacqueline Ryan; Nelson, Andrew J. (AoIR Selected Papers of Internet Research, 2013)
“Advice animals” are popular user-created, image-based (.gif), online meme formats. The memes include a humorous image of an animal juxtaposed with text offering advice and/or making a joke. One such example is known as “Confession Bear”, which features a sad looking Malayan sun bear “confessing” to something silly, shameful, taboo, or embarrassing. Confession Bear was first circulated through the online community Reddit and was intended to be humorous. However, users unexpectedly started creating and sharing more serious confessions involving topics such as rape, abuse, and addiction. These more serious confessions juxtaposed with the “Confession Bear” image spurred lengthy in-depth conversations on the Reddit message boards about the validity, authenticity, and appropriateness of such confessions. Some users argued advice animals were not “supposed” to be serious, claiming these confessions were an inappropriate use of the form; as such, some users attempted to police the participatory culture created by the production of image-based memes. Others sought to find the “truth” in the claims; some argued the confessions were false and therefore inappropriate, while others defended the confessions as authentic, and therefore appropriate. This paper argues anonymity allows users to appropriate and repurpose humorous image-based memes in ways that simultaneously challenge and reproduce hegemonic culture.